Defining Nature-Based Solutions Within the Blue Economy: The Example of Aquaculture - Hughes, Adam D. (Frontiers in Marine Science, 2021)
The concepts of Nature-based Solutions (NbS) and the Blue Economy (BE) are two prominent sustainability frameworks at the forefront of policy dialogues. However, investment within the BE has been slowed by the lack of a sufficiently robust operational definition. This lack of definition reduces investor confidence and impacts adoption by policy makers and practitioners. By considering the overlap between the two sustainability frameworks it is possible to identify specific sectors and activities within the BE that also fit the operationalised criteria for NbS. Undertaking this process for one sector of the BE (aquaculture) has provided evidence that aquaculture activities, if planned and operated within the criteria, would qualify as NbS and as such may unlock financing for the provision of ecosystem services.